Effect of Surface Roughness on the Friction Moment in a Lubricated Deep Groove Ball Bearing - Harsh Kumar; Vaibhav Gupta; Velamala Bharath; Mayank Tiwari; Surajit Kumar Paul; Lokesh Agrawal; Arendra Pal Singh; Ayush Jain (Lubricants)
Deep groove ball bearings (DGBBs) are extensively utilized in industrial machinery, mechanical systems, and household appliances due to their simple design, low maintenance, and ability to operate at high speeds. A critical issue in the performance of these bearings is the power loss by internal friction torque, which adversely affects system efficiency, longevity, and reliability, particularly in demanding applications such as aviation and marine systems. The friction torque in DGBBs is influenced by factors such as load, speed, surface roughness, and lubricant viscosity, making the precise understanding of these elements essential for optimizing system efficiency. Despite its significance, the effect of surface roughness on friction torque in DGBBs remains underexplored. This paper presents an analytical model to evaluate the frictional moments resulting from interactions between the ball–race and ball–cage in lubricated, low-speed DGBBs. This model employs a mixed elastohydrodynamic lubrication approach to determine the friction coefficient at the contact interfaces. This study explores how surface roughness and speed affect both ball–race and ball–cage friction torque, offering a comprehensive analysis of their influence on overall frictional torque. Additionally, the effect of surface roughness on ball–cage contact forces is investigated, enhancing the understanding of its contribution to friction torque. These insights aim to improve DGBB design and operation, maximizing performance and energy efficiency.